Brain metastases: It takes two factors for a primary cancer to metastasize to brain - Liu, Dingyun; Bai, Jun; Chen, Qian; Tan, Renbo; An, Zheng; Xiao, Jun; Qu, Yingwei; Xu, Ying (Frontiers in Oncology, 2022)
Brain metastasis of a cancer is a malignant disease with high mortality, but the cause and the molecular mechanism remain largely unknown. Using the samples of primary tumors of 22 cancer types in the TCGA database, we have performed a computational study of their transcriptomic data to investigate the drivers of brain metastasis at the basic physics and chemistry level. Our main discoveries are: (i) the physical characteristics, namely electric charge, molecular weight, and the hydrophobicity of the extracellular structures of expressed transmembrane proteins largely affect a primary cancer cell’s ability to cross the blood-brain barrier; and (ii) brain metastasis may require specific functions provided by the activated enzymes in the metastasizing primary cancer cells for survival in the brain micro-environment. Both predictions are supported by published experimental studies. Based on these findings, we have built a binary classifier to predict if a given primary cancer may have brain metastasis, achieving the accuracy level at AUC = 0.92 on large test sets.